(untitled) (London, 2001)
The book defines ecotoxicology as the study of the harmful effects of chemicals upon ecosystem. The first section of the book describes the major classes of orgamic and inorganic pollutants, their properties, release and environmental fate, and transport in air, water and along food chains. The second section deals with the effects of pollutants upon individual organisms, covering: toxicity testing, potentiation, biochemical, and physiological effects, in situ biomonituring, and biomaker assays to measure exposure and toxic effects. The final section deals with effects at the level of population, community, and ecosystem. Effects on numbers, gene frequencies, ecosystem function and the use of biomarker assays are also discussed
Độc chất học sinh thái
Keywords: Ô nhiễm,Pollution; Diện mạo môi trường,Environmental aspects